VD_FINDINFO HC / 2019 / 1078 vom 20. Dezember 2019 - VD Tribunal cantonal (2019)
FAIT DE DOUBLE PERTINENCE, COMPÉTENCE RATIONE MATERIAE, BAIL À LOYER | 237 CPC (CH), 59 al. 2 let. b CPC (CH), 60 CPC (CH), 1 al. 1 LJB, 2 al. 1 LJB